An Analysis of the Constitutional Foundations on the Devolution of State Authority in Africa : A Comparative Study - Bekink, Bernard (University of Pretoria, 2024)
Dissertation (LLM (Constitutional and Administrative Law))--University of Pretoria, 2024.